PENDIDIKAN KARAKTER MELALUI PENGELOLAAN SAMPAH BERBASIS LINGKUNGAN DI DESA MUNTUK DLINGO - Gunartati -; Choirun Nisaa (DHARMA BAKTI, 2018)
Bantul regency government has mobilized all elements of society to care about the cleanliness of the environment, like through good waste management in several places and including in the tourist attractions. Muntuk Village, Dlingo, Bantul is one of the beautiful tourist destinations that attract many tourists, need to get intense attention about the environment in order to stay clean and beautiful. The objectives of community service are to: (1) motivate Muntuk village community's care about the surrounding environment, (2) provide character education to the community to form conscious behavior of waste, (3) provide non-organic waste management training that implemented on 30 December 2017. Furthermore, cadres have been formed to continue pioneering waste management. And considering the limited time, funds and personnel then to follow up the community service activities will be followed by the cadres with the coordination of research institutions and dedication to the community STKIP Catur Sakti Yogyakarta.